Role of Somatostatin in Preventing Post-endoscopic Retrograde Cholangiopancreatography (ERCP) Pancreatitis: An Update Meta-analysis - Hu, Jing; Li, Pei-Lin; Zhang, Tao; Chen, Jin-Ping; Hu, Yao-Jun; Yu, Zheng; Wang, Jin-Peng; Zhu, Dan; Tong, Xiao-Fei (Frontiers in Pharmacology, 2016)
Background: Acute pancreatitis is the most common serious complication of endoscopic retrograde cholangiopancreatography (ERCP). Although somatostatin (SOM) has been used in the prevention of post-ERCP pancreatitis (PEP), the efficacy of SOM remains inconsistent. Methods: Electronic databases, including PubMed/MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials (CENTRAL, The Cochrane Library), and the Science Citation Index were searched to retrieve relevant studies. Details of the study population, including patients’ characteristics, sample size, regimen of drug administration and incidence of PEP, hyperamylasemia and abdominal pain were extracted by two investigators. Data were analyzed with Review Manager 5.3 software. Results: Eleven randomized controlled trials (RCTs), enrolling a total of 4192 patients, were included in the meta-analysis. After data were pooled, we observed decreased incidence of ERCP-induced outcomes, such as PEP (RR=0.63, 95% CI: 0.40, 0.98; P=0.04) and hyperamylasemia (RR=0.75, 95% CI: 0.66, 0.84; P<0.001) in patients treated with SOM than those with placebo. Subgroup analysis by ethnicity found decreased incidence of PEP and hyperamylasemia in Asia only. Subgroup analysis by treatment schedule and dosage revealed decreased incidence of PEP and hyperamylasemia when SOM were treated with a single bolus or long-term infusion, or at dose above 3000 μg. We did not observed efficacy of SOM on abdominal pain in pooled or subgroup analysis. Conclusion: This meta-analysis of patients undergoing ERCP showed reduced incidence of PEP and hyperamylasemia when SOM was administrated with single bolus, long-term infusion, or high dosage. More data are needed to confirm our findings.